Imaginea periferiei în proza lui Vasile Demetrius - Alexandru Farcaș (Revista de Istorie și Teorie Literară)
This paper aims to showcase one of the two ways to imagine Bucharest suburbs active in the fiction before the Great War. Based on the narrative strategies of Naturalism, V. Demetrius’ „sympathetic” approach, draping up in tragedy the economic realities of life in the new industrial peripheries, appears to us as basically opposed to I.L. Caragiale’s critical perspective, more focused on the moral and psychological issues of the marginal milieux.